2021
DOI: 10.3892/mco.2021.2262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic variables in chronic lymphocytic leukemia and association with disease stage

Abstract: The aim of the present study was to investigate different biological prognostic markers to identify high-risk patients with chronic lymphocytic leukemia (CLL) with a higher tumor burden, in order to ensure appropriate management. A total of 81 Egyptian patients with CLL were enrolled in the present study, with 75 healthy subjects serving as the control group. The expression of CD49d, CD38 and ZAP-70 in CLL cells was assessed using flow cytometry. The fluorescence in situ hybridization te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…It is a critical regulator of CLL cell migration, allowing tumor cells to pass from the blood to the protective microenvironment of LN and BM. [46] The high level in patients with B-CLL is associated with an aggressive course of the disease and is considered one of the negative prognostic markers [47]. In this series of cases, it was found that 65.6% of the patients expressed CD49d, results that coincide with those of the study carried out by Al-Rubaie HA et al [48] in Iraq that showed positivity for CD49d (60%).…”
Section: Discussionsupporting
confidence: 79%
“…It is a critical regulator of CLL cell migration, allowing tumor cells to pass from the blood to the protective microenvironment of LN and BM. [46] The high level in patients with B-CLL is associated with an aggressive course of the disease and is considered one of the negative prognostic markers [47]. In this series of cases, it was found that 65.6% of the patients expressed CD49d, results that coincide with those of the study carried out by Al-Rubaie HA et al [48] in Iraq that showed positivity for CD49d (60%).…”
Section: Discussionsupporting
confidence: 79%
“…Out of total 10/73 (13.4%) patients 4 (40%) showed positive results and 6 (60%) negative results. Attia HR et al, 18 documented in their study that in the Binet staging system, there was a noteworthy increase in the expression of ZAP-70 in group C patients compared to groups A and B (p-value 0.008, 0.034 and 0.017 respectively ) which were linked to higher CD38 expression, hepatomegaly, splenomegaly, and specific genetic markers. This study showed a more comprehensive analysis of prognostic markers with males being more prevalent as in our study.…”
Section: Discussionmentioning
confidence: 93%